Primary T-Cell Lymphoma of the Prostate in a Dog – Case Report - Costa, Marina Laudares; Fonseca-Alves, Carlos Eduardo; Oliveira, Gustavo Garkalns de Souza; Nakage-Canesin, Ana Paula Massae; Rezende, Paula Christine Bonadio; Demarchi Munhoz, Thiago (Brazilian Journal of Case Reports, 2024)
The prostate gland is considered an accessory sexual organ of the male reproductive system which in dogs can vary in size influenced by age, weight and breed. The most frequent anomalies found in the canine prostate are due to Benign prostatic hyperplasia, prostatitis, abscesses, prostatic and paraprostatic cysts, squamous metaplasia and prostate neoplasia in adult and geriatric dogs. Prostate lymphoma, unlike some neoplasms, is not routinely seen. An abnormal prostate is presumptively diagnosed based on the patient’s history and clinical signs, blood markers and abnormal anatomical outline detected on palpation and imaging. The present report describes the case of a 13-year-old male, 26 kg, intact dog, referred to the Centro Universitário Barão de Mauá Veterinary Campus manifesting dysuria and diagnosed with primary prostatic lymphoma.